The Modalities of Psychoanalysis. an Analysis of the Contemporary Psychoanalytic Map from the Contributions of Philosophy; [Las Modalidades del Psicoanálisis. Un Análisis Al Mapa Psicoanalítico Actual Desde Los Aportes de la Filosofía] - Letelier-Soto, A (Universidad de Caldas, 2023)
The problem and debate on the disjunction of philosophy and the psychoanalytic clinic is a phenomenon that has brought several discussions from both theoretical sides. This paper addresses some of the most recent contributions to the philosophical debate in implication with the modifications of the current psychoanalytic clinic. Our objective was to contribute to the clarification of the fundamental tools that philosophy provides to the modification of psychoanalytic theory and practice through a documentary analysis with a theoretical-critical approach. To this end, we have traced a general historical overview of the modifications and arguments that have emerged throughout the history of psychoanalysis. Finally, we expose some of the pending debates and theses to continue exploring, in view of the mixture of knowledge and for the benefit of reflections and analysis focused on the human condition, issues that both philosophy and psychoanalysis have as central axes. © (2023), (Universidad de Caldas). All Rights Reserved.